2022
DOI: 10.3847/1538-4357/ac4ae7
|View full text |Cite
|
Sign up to set email alerts
|

CHANG-ES. XXIV. First Detection of a Radio Nuclear Ring and Potential LLAGN in NGC 5792

Abstract: We report the discoveries of a nuclear ring of diameter 10″ (∼1.5 kpc) and a potential low-luminosity active galactic nucleus (LLAGN) in the radio continuum emission map of the edge-on barred spiral galaxy NGC 5792. These discoveries are based on the Continuum Halos in Nearby Galaxies—an Expanded Very Large Array (VLA) Survey, as well as subsequent VLA observations of subarcsecond resolution. Using a mixture of Hα and 24 μm calibrations, we disentangle the thermal and nonthermal radio emission of the nuclear r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Figure 1(c) shows the linear polarization map obtained from our D-configuration L-band data, the map is superimposed with the magnetic field orientations and Stokes I contours. The vertically oriented cylindrical structure along the jet axis reveals the bipolar polarization lobes, which is AGN related (Yang et al 2022). These polarization segments are perpendicular to the bipolar polarization lobes, indicating the presence of a helical/toroidal magnetic field component traveling outward with the jet.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 1(c) shows the linear polarization map obtained from our D-configuration L-band data, the map is superimposed with the magnetic field orientations and Stokes I contours. The vertically oriented cylindrical structure along the jet axis reveals the bipolar polarization lobes, which is AGN related (Yang et al 2022). These polarization segments are perpendicular to the bipolar polarization lobes, indicating the presence of a helical/toroidal magnetic field component traveling outward with the jet.…”
Section: Resultsmentioning
confidence: 97%
“…Nuclear rings at the centers of barred galaxies are active in star formation (Mazzuca et al 2008;Ma et al 2018) and threaded by magnetic fields with a mean strength of ∼50-100 μG (Beck et al 2005;Yang et al 2022). To study how magnetic fields affect star formation in nuclear rings, we run MHD simulations of galactic centers.…”
Section: Discussionmentioning
confidence: 99%
“…Observations show that nuclear rings in real galaxies are quite strongly magnetized. Assuming energy equipartition between magnetic fields and cosmic rays (CRs), the average magnetic field strengths in nuclear rings inferred from radio synchrotron observations are estimated to be ∼55 μG for NGC 1097 (Beck et al 2005), ∼63 μG for NGC 1365 (Beck et al 2005), and ∼84 μG for NGC 5792 (Yang et al 2022), much stronger than in spiral arms of normal disk galaxies (Beck 2015). Beck et al (1999Beck et al ( , 2005 mapped radio continuum emission in barred galaxies and found that the magnetic fields are predominantly parallel to the dust lanes, while penetrating the nuclear rings with a large pitch angle (∼40°).…”
Section: Introductionmentioning
confidence: 99%
“…On the left, polarization contours plus B-field orientations over a grayscale optical SDSS image of NGC 5792, from [39]. On the right, L-band total intensity contours over the B/L to C/C spectral index map of NGC 3628 [24].…”
Section: Into the Core-active Galactic Nucleimentioning
confidence: 99%